Vibrio cholerae: disease, clinical manifestations and microbiology - Josué Guilherme Lisbôa Moura; Tanise Gemelli; Jessica Muller (Universidade de Santa Cruz do Sul, 2018)
Justification and content: Cholera is an acute intestinal infectious disease caused by the toxin of Vibrio cholerae. Transmission is oral-fecal and occurs predominantly in contaminated aquatic environments. It can be fatal, but it is easily avoided and treated. Its propagation is associated with lack of basic sanitation because it grows exponentially in environments. The diagnosis is clinical-epidemiological, laboratory with selective media for the micro-organism and rapid test, the latter is not sensitive or specific. Treatment is with oral rehydration salts and antibiotic therapy, zinc supplementation is indicated. There is vaccination for Vibrio cholerae, and this is the best measure for the control of the disease. Conclusion: Cholera research is no longer frequent, as it is considered a disease of countries that are not developed. In this context, research is still needed on sewage systems, effluent monitoring, public water supply quality surveillance and food quality monitoring.